1991
DOI: 10.3168/jds.s0022-0302(91)78163-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Methionyl Bovine Somatotropin (Sometribove) in High Producing Cows Milked Three Times Daily

Abstract: Effects of daily sometribove administration on milk yield and composition, body condition score, BW, and SCC were evaluated in Holstein cows milked three times daily. Lactating cows (n =104) were assigned randomly to control or sometribove-treated (25 mg/d) groups. The experimental period was 16 wk, consisting of 2-wk pretreatment, 12-wk treatment, and 2-wk posttreatment periods. All cows were injected once daily starting at 53 to 180 d postpartum, housed in free stalls, and fed one of five total mixed rations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Two recent reports describe the response of frequently-milked cows to bGH. A 14 d bGH preparation produced a 10-8% increase in yield in cows milked four times daily (Armstrong et al 1990), while a daily injection of 25 mg bGH increased yield by 18-8% in thrice-daily milked cows (Jordan et al 1991). Neither study included a twice-daily milked control group, so the absolute increase above 'normal' twicedaily milking cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reports describe the response of frequently-milked cows to bGH. A 14 d bGH preparation produced a 10-8% increase in yield in cows milked four times daily (Armstrong et al 1990), while a daily injection of 25 mg bGH increased yield by 18-8% in thrice-daily milked cows (Jordan et al 1991). Neither study included a twice-daily milked control group, so the absolute increase above 'normal' twicedaily milking cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Increases of 20 to 40% in milk yield for dairy cows receiving bST were shown by Bauman et al (3). Jordan et al (9) found that bST treatment for high-producing cows increased milk yield and protein percentage by 18.8 and 3.3%, respectively, but that there were no effects on SCC and BW. A review by Bauman (2) reported that bST increased milk yield, cows remained healthy, the composition of milk was not changed and that milk response to bST would be negligible if bST-treated cows were not stressed, underfed, or sick because of poor management.…”
Section: Introductionmentioning
confidence: 91%
“…In addition to problems with mastitis, there is also concern that rbST treatment may increase the risk of lameness and foot and leg disorders. While many early studies failed to find a detectable difference between rbST treated and control animals [ 121 , 125 , 126 , 127 , 128 , 129 ], others found a slight increase in the number of cows culled due to lameness [ 130 ] and slightly more feet and leg problems [ 130 , 131 ]. As with the early work on mastitis and rbST, in studies with small cow numbers, low statistical power may have prevented detection of effects, and slight increases would be hard to find.…”
Section: Mitigation Strategies and Possible Negative Animal Welfarmentioning
confidence: 99%